Multistrain Probiotics and their Role in Presentation of Severity and Frequency of Upper Respiratory Tract Infection - Iqra Aslam, Sadaf Hammad, Sohaib Farooq, Ahmad Yar, Nauman Ahmed, Sherjeel Fazal (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Upper respiratory tract infections (URTIs) are a leading cause of morbidity and unnecessary antibiotic use globally. Objective: To evaluate the effect of multistrain probiotic supplementation on the frequency, severity, and duration of URTIs in a cohort of individuals with a history of recurrent respiratory infections. Methods: This descriptive, observational study was conducted at Lahore General Hospital, Lahore from 5 Jan 2023 to 10 July 2023. A total of 135 patients were enrolled using non-probability consecutive sampling. Baseline demographic information, medical history, nutritional status, and previous URTI frequency over the past 12 months were recorded using a standardized questionnaire. During the 12-week intervention period, participants were instructed to record any new URTI episodes, symptom duration, and severity using a daily symptom diary. Results: The mean number of URTI episodes declined from 4.2 ± 1.1 to 1.3 ± 0.9 (p < 0.001). Symptom severity scores decreased from 7.6 ± 1.9 to 3.4 ± 1.2, and the average duration of illness per episode dropped from 6.1 ± 2.3 days to 3.0 ± 1.5 days (p < 0.001). Antibiotic usage reduced from 47.4% to 13.3%, and the number of missed work or school days fell from 3.8 ± 1.7 to 1.4 ± 0.8 per episode (p < 0.001). The intervention was well tolerated, with no serious adverse events and a compliance rate of 89.6%. Conclusion: It is concluded that multistrain probiotics reduce the frequency, severity, and duration of upper respiratory tract infections and may decrease the need for antibiotics and associated absenteeism. These findings support the inclusion of probiotics in preventive strategies for respiratory health. Further randomized trials are recommended to validate these outcomes and refine optimal probiotic combinations. Keywords: Multistrain probiotics, upper respiratory tract infection, severity, immune modulation, antibiotic use.